Geometry‐Directed Self‐Assembly of Polymeric Molecular Frameworks. (15th December 2020) - Yan, Xiao‐Yun; Guo, Qing‐Yun; Lin, Zhiwei; Liu, Xian‐You; Yuan, Jun; Wang, Jing; Wang, Haomin; Liu, Yuchu; Su, Zebin; Liu, Tong; Huang, Jiahao; Zhang, Ruimeng; et al.
Abstract: Despite the significant advances in creating assembled structures from polymers, engineering the assembly of polymeric materials into framework structures remains an outstanding challenge. In this work, we present a facile strategy to construct polymeric molecular frameworks through the assembly of T‐shape polymer‐rod‐sphere amphiphiles in the bulk state. Various frameworks are yielded as a result of delicate interplays among three components of the T‐shape amphiphiles. The internal structure of frameworks was revealed by combining experimental investigations and computational simulations. The frameworks display good solution‐processability, thermal stability, and uniform pore‐forming capability, which endow the resultant frameworks with great potential in scalable fabrications. Abstract : A facile strategy to construct a solution‐processable, thermally stable, polymeric framework‐like material is presented. The structure is prepared by the self‐assembly of T‐shape rod‐sphere‐polymer amphiphiles. During the process of self‐assembly, each component in the amphiphile plays its own roles and they mutually interact with each other. Once the polymer chains are selectively decomposed, highly ordered mesoporous structures are produced.